L. W. Moultrie, Charter and Ordinances of the City of Fresno 37, § 53 (1896) - (:unkn) unknown (My University, 1896)
Prohibited the transfer to any minor under the age of 18 any gun, pistol or other firearm, dirk, Bowie knife, powder, shot, bullets, or any combustible or dangerous material, absent written consent of parent or guardian.
Keywords: TRANSFER - MINORS